Dyadic coping responses and partners' perceptions for couple satisfaction: An actor–partner interdependence analysis. (August 2015) - Donato, Silvia; Parise, Miriam; Iafrate, Raffaella; Bertoni, Anna; Finkenauer, Catrin; Bodenmann, Guy
Applying the actor–partner interdependence model to 114 couples' data, we examined the link between partners' change in reported dyadic coping responses from 6 months before marriage to 12 months after marriage and change in the perceptions of the other's dyadic coping responses, the role of these associations for partners' change in relationship satisfaction, and the role of gender in these relations. Results highlighted both accuracy and projection effects in partners' perceptions. Moreover, one's perceptions of the other's dyadic coping responses mediated the effect of both one's own and the others' reported dyadic coping behaviors on one's satisfaction. Findings are discussed in light of the implications for the study of dyadic coping and partner support as well as for intervention.